Rutrends and prospects of educational and clinical work on the results of the 10th International Symposium of Clinical and Applied Anatomy - Dydykin, S.S.; Kytko, O. V.; Vasil’ev, Y. L.; Shcherbyuk, A.N.; Kapitonova, Marina (Indo American Journal of Pharmaceutical Sciences(IAJPS), 2018)
September 13 - 16, 2018, the 10th International Clinical and Applied Anatomy Symposium (ISCAA 2018) was held at the site of the Department of Operative Surgery and Topographic Anatomy of the Medical Faculty of Sechenov University. Russian scientists in a tense struggle won half of the honorary diplomas of the symposium, presenting bright, well-prepared and decorated, lectures and speeches. Confirmation of the leading position of Sechenov University among the medical schools of Russia is that among the 17 participants of the symposium who were awarded honorary diplomas - 6 are its representatives. Abstracts that have been selected by the Symposium Program Committee are printed in a special issue of the Morphology journal.